Profound sensorineural hearing loss after one cycle of intraperitoneal cisplatin in treatment of advanced ovarian cancer - Megan E. McDonald; Jordan Mattson; Emily Hill (Elsevier, 2017)
Few advances in the treatment of advanced epithelial ovarian cancer have improved patient overall survival. However, the incorporation of intraperitoneal administration of platinum based chemotherapy to standard treatment was one such advancement. It is understood that the intraperitoneal regimen is associated with increased toxicity when compared to intravenous administration alone; however, information regarding the specific risk of ototoxicity is lacking in the literature. We report a case of almost complete sensorineural hearing loss after one cycle of intraperitoneal cisplatin. Three days after receiving an intravenous 24 h paclitaxel at 135 mg/m2 and subsequent intraperitoneal infusion of cisplatin at 75 mg/m2, the patient presented with profound bilateral sensorineural hearing loss. The patient experienced no recovery of hearing despite an aggressive systemic steroid taper and change in chemotherapy regimen to alternative agents. She is currently under consideration for cochlear device implantation. Generally, cisplatin related ototoxicity during treatment of epithelial ovarian cancer is gradual, limited to high-frequency ranges and dose-related; however, the toxicity with only one standard dose can be profound and irreversible. This risk should be addressed when counseling patients prior to initiation of treatment.